Global Trends in Higher Education Policies - Moyle, Prof. Kathryn (Sebelas Maret University, 2016)
This paper outlines the current global context for higher education in 2015, as a basis for examining the key trends in teacher education in the first decades of the 21st century. The purpose of this paper is to outline the current global contexts for higher education, and to provide an overview of the policies found in teacher education in those countries that consistently produce students who perform highly on international standardized tests such as PISA, TIMSS and PIRLS. The policies guiding teacher education in âhigh-performingâ countries tends to be aligned and inter-connected. These policies include public investment in education; creating identifiable career paths in teaching; attracting high-quality applicants; employing effective quality assurance policies and procedures; working in partnership with schools to train teachers; and using research and enquiry as a way to develop an informed, reflective, teaching profession. The paper then identifies broad principles that can be used to inform the development of future teacher education policies.This paper outlines the current global context for higher education in 2015, as a basis for examining the key trends in teacher education in the first decades of the 21st century. The purpose of this paper is to outline the current global contexts for higher education, and to provide an overview of the policies found in teacher education in those countries that consistently produce students who perform highly on international standardized tests such as PISA, TIMSS and PIRLS. The policies guiding teacher education in âhigh-performingâ countries tends to be aligned and inter-connected. These policies include public investment in education; creating identifiable career paths in teaching; attracting high-quality applicants; employing effective quality assurance policies and procedures; working in partnership with schools to train teachers; and using research and enquiry as a way to develop an informed, reflective, teaching profession. The paper then identifies broad principles that can be used to inform the development of future teacher education policies.